P-284 Dipping a toe in the water: developing professional roles from within. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Birch, Helen; Groves, Karen; Ainsworth, Catherine; Webster, Laura
Abstract : Aim: Experienced, qualified and unqualified, hospice nurses desire career progression which is limited within the hospice environment. Time and money is invested in education to deliver high quality palliative care. For nurses to then take those skills elsewhere leaves a huge gap in our workforce. An NHS post is the usual route to becoming a Palliative Care Nurse Specialist (PCNS). If experienced Health Care Assistants (HCA) want to progress they are currently required to attend university to gain an academic qualification and for many this would prove challenging. Approach: Local hospices' professional development was scoped, but revealed no specific models and new roles were bespoke. Two local roles were developed; Hospice Nurse Specialist (HNS), and HCA Therapy Assistant (TA). Roles were clearly defined, with robust job descriptions and person specifications, scope of practice agreed, required skills, competences and boundaries established. Result: The skilled HNS provides continuity of care for patients and a visible presence provides a vital link between nursing and medical professionals. It has led to a more streamlined admission process for the patient and following completion of the non-medical prescribing module, the HNS works autonomously wherever the patient presents, allowing medical staff to focus on patients with more specialist complex needs. The TA role presented its own challenges as there is no national specifically defined pathway to follow. Specific competencies were developed including input from community equipment suppliers, wheelchair services and by shadowing various therapy teams within hospital and community setting. Conclusion: This has been a successful 'dip of the toe in the water' for role development. Future development includes an accredited academic module in Specialist Palliative and End of Life Care, in partnership with the local university and investigating the role of apprenticeships for hospice Healthcare Support Workers and Assistant Practitioners.